(untitled) (Journal of Universal Science Research, 2025)
The article analyzes the epidemiology of Mycobacterium tuberculosis, the causative agent of tuberculosis (TB). The prevalence and risk factors of tuberculosis, including social, economic conditions and the state of the healthcare system, are considered. Based on statistical data, the global distribution of the disease, high-risk groups (for example, those with weakened immune systems) and regions are identified. The article also discusses the resistance of M. tuberculosis to treatment, vaccine effectiveness and new diagnostic methods. Global and local strategies for the prevention of TB, as well as ways to overcome the disease are proposed.